SECOND TYPE INTEGRAL CONDITIONAL PROBLEM FOR A LOADED MIXED PARABOLIC EQUATION - I.M. Moydinov (Western European Studies, 2024)
In this article, the one-valued solution of the integral conditional problem for the mixed parabolic equation with perpendicular time directions is studied
Keywords: Mixed parabolic equation; mixed parabolic equation; integral condition